Cerebral Venous Thrombosis: Clinical, Radiological, Biological, and Etiological Characteristics of a French Prospective Cohort (FPCCVT)—Comparison With ISCVT Cohort - Triquenot Bagan, Aude; Crassard, Isabelle; Drouet, Ludovic; Barbieux-Guillot, Marianne; Marlu, Raphaël; Robinet-Borgomino, Emmanuelle; Morange, Pierre-Emmanuel; Wolff, Valérie; Grunebaum, Lelia; Klapczynski, Frédéric; André-Kerneis, Elisabeth; Pico, Fernando; et al. (Frontiers in Neurology, 2021)
Introduction: Cerebral venous thrombosis (CVT) is a rare disease with highly variable clinical presentation and outcome. Etiological assessment may be negative. The clinical and radiological presentation and evolution could be very variable. The mechanisms involved in this variability remain unknown. Objective: The aim of this multicenter French study registered on ClinicalTrials.gov (NCT02013635) was therefore to prospectively recruit a cohort of patients with cerebral venous thrombosis (FPCCVT) in order to study thrombin generation and clot degradation and to evaluate their influence on clinical radiological characteristics. The first part of the study was to compare our cohort with a reference cohort to validate, later our biological results. Methods: This prospective, multicenter, French study was conducted from July 2011 to September 2016. Consecutive patients (aged >15 years) referred to the stroke units of 21 French centers and who had a diagnosis of symptomatic CVT were included. All patients gave their written informed consent. The diagnosis of CVT had to be confirmed by imaging. Clinical, radiological, biological and etiological characteristics were recorded at baseline, at acute phase, at 3 months and at last follow-up visit. Thrombophilia screening and the choice of treatment were performed by the attending physician. All data were compared with data of International Study of CVT published by Ferro et al. Results: Two-hundred-and-thirty-one patients were included: 117 (50.6%) had isolated intracranial hypertension, 96 (41.5%) had focal syndrome, During hospitalization, 229 (99.1%) patients received anticoagulant treatment. Median length of hospital stay was 10 days. Five patients died during hospitalization (2.2%). At 3 months, 216 patients (97.0%) had follow-up with neurological data based on an outpatient visit. The mean duration of antithrombotic treatment was 9 months and the mean time to last follow-up was 10.5 months. Completeness of follow-up was satisfactory with only 7.8% of patients lost at the end of the study. At least one risk factor was identified in 200 patients. Conclusions: In this first part of the study, we demonstrated that the FPCCVT had clinical, radiological, biological and etiological characteristics similar of the ISCVT cohort. This last cohort is still today the largest international cohort and therefore represents a reference.